Positive alternatives to exclusion - Cooper, Paul, 1955- (Routledge, 2000)
"This book looks at what schools can do to build more harmonious communities and engage students - particularly those at risk of exclusion - more productively in all areas of school life. It describes the Positive Alternatives to School Exclusion Project, a partnership research study, based at the School of Education, University of Cambridge. This was a multi-phase (primary, secondary, FE) empirical study of the thinking underlying what schools and colleges were currently doing to foster inclusion, and to reduce and prevent exclusion."